cAMP-stimulated transcription of DGKθ requires steroidogenic factor 1 and sterol regulatory element binding protein 1 - Cai, Kai (The American Society for Biochemistry and Molecular Biology, 2013)
Diacylglycerol kinase (DGK)θ is a lipid kinase that phosphorylates diacylglycerol to form phosphatidic acid (PA). We have previously shown that PA is a ligand for the nuclear receptor steroidogenic factor 1 (SF1) and that cAMP-stimulated expression of SF1 target genes requires DGKθ. In this study, we sought to investigate the role of cAMP signaling in regulating DGKθ gene expression. Real time RT-PCR and Western blot analysis revealed that dibutyryl cAMP (Bt(2)cAMP) increased the mRNA and protein expression, respectively, of DGKθ in H295R human adrenocortical cells. SF1 and sterol regulatory element binding protein 1 (SREBP1) increased the transcriptional activity of a reporter plasmid containing 1.5 kb of the DGKθ promoter fused to the luciferase gene. Mutation of putative cAMP responsive sequences abolished SF1- and SREBP-dependent DGKθ reporter gene activation. Consistent with this finding, chromatin immunoprecipitation assay demonstrated that Bt(2)cAMP signaling increased the recruitment of SF1 and SREBP1 to the DGKθ promoter. Coimmunoprecipitation assay revealed that SF1 and SREBP1 interact, suggesting that the two transcription factors form a complex on the DGKθ promoter. Finally, silencing SF1 and SREBP1 abolished cAMP-stimulated DGKθ expression. Taken together, we demonstrate that SF1 and SREBP1 activate DGKθ transcription in a cAMP-dependent manner in human adrenocortical cells.